Comparison of the Impulse the New BETA Volleyball Designed With Other Volleyballs Samples - Mohsen Bargahmadi; Ehsan Fakhri Mirzanag; Safa Seraj Mahdizadeh (Biyumikānīk-i varzishī, 2022)
Background and aim The sport of volleyball requires constant contact of sports balls with the hands of athletes, Therefore, the sports balls used in volleyball can play an important role in the performance of athletes. therefore, the aim of the present study is to compare the impulse of the new BETA volleyball designed with other samples volleyballs using the Bertak model force plate made in the United States. Material and Methods Examples of Mikasa volleyballs, model V200W, made in Japan, Fox volleyball, model Spain, made in France and Old and new BETA volleyballs made in Iran with a weight range of 260 to 270 grams with a circumference of 66 cm were used in the present study, Finally, the impulses of volleyballs were compared using a Bertek model force plate machine. Results In line with the findings of the present study, there is a significant difference between the impulse of the sample of the new BETA volleyball ball designed at compared to the volleyball sample of the old beta design in the direction of the vertical axis (P = 0.014). in this regard, the post hoc test showed that there is no statistically significant difference between the sample of the new BETA volleyball at compared to the sample of Fox volleyball (P = 0.102) and Mikasa volleyball that is used in official competitions (P = 0.662). Conclusion Therefore, the use of a new BETA volleyball designed to reduce the rate of sports injuries is recommended to all coaches, referees, athletes and officials in the field of volleyball.